2011
DOI: 10.1111/j.1365-2559.2011.03792.x
|View full text |Cite
|
Sign up to set email alerts
|

Topographical, morphological and immunohistochemical characteristics of carcinoma in situ of the breast involving sclerosing adenosis. Two distinct topographical patterns and histological types of carcinoma in situ

Abstract: Most CIS involving SA arises within SA and high-grade DCIS tends to grow beyond SA. Occasional CIS may arise outside SA and secondarily involve SA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
0
15
1
1
Order By: Relevance
“…According to the current study, about 36.4% cases of SA-BC were underestimated as benign adenosis or ADH at CNB. One possible explanation for these false-negative results might be that cancer within the extensive SA tends to be limited or occurs preferentially at the periphery of SA, peculiarly in those early stage tumours, therefore there is a risk of sampling inaccuracy/inadequacy for CNB 8. Moreover, the overall architecture of SA-BC is not consistently recognisable in those small CNB samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the current study, about 36.4% cases of SA-BC were underestimated as benign adenosis or ADH at CNB. One possible explanation for these false-negative results might be that cancer within the extensive SA tends to be limited or occurs preferentially at the periphery of SA, peculiarly in those early stage tumours, therefore there is a risk of sampling inaccuracy/inadequacy for CNB 8. Moreover, the overall architecture of SA-BC is not consistently recognisable in those small CNB samples.…”
Section: Discussionmentioning
confidence: 99%
“…The stroma in SA-CIS is mainly composed of proliferated collagen and fibrosis, compared with more cellular desmoplastic stroma in invasive carcinoma. Identification of myoepithelial cells surrounding the atypical glands by careful inspection and auxiliary IHC staining can rule out the possibility of invasive carcinoma 8. Another situation that may cause confusion with SA-BC is SA with florid hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20,21 Some studies have previously demonstrated that SA cases are often considered to be hormone positive. 22 …”
Section: Discussionmentioning
confidence: 99%